Bilateral wrist robot-assisted training in chronic hemiplegic stroke: A pilot study. Issue 2 (January 2015) - Kim, Eunjoo; Lee, Jeong-Ah
Abstract: Background: The stroke population needing physical rehabilitation of the upper extremity is constantly increasing. To solve this problem, robot devices for improving motor performance are developed to assist physical rehabilitation in Korea. The aim of this study was to develop the robot-assisted wrist training system and to apply this to the chronic hemiplegic stroke participants. Methods: Bilateral wrist robotic device was developed and we applied this to four chronic hemiplegic stroke participants. Robot-assisted wrist training system was assessed by Hand grip force, Medical Research Council, Range of motion, Upper extremity Fugl-Meyer Assessment, and Motor Activity Log. In addition, we measured functional magnetic Resonance Imaging (fMRI) analysis for cortical reorganization during both hand movement. Participants received 60 min, 20 sessions, five days a week, for four consecutive weeks. The assessments were done before and after 20 training sessions Results: Robot-assisted wrist training system was built with the bilateral wrist flexion/extension and pronation/supination performance that provides a repetitive active-active, active-passive, and passive-passive mode. Muscle strength, Motion of wrist, and motor function were enhanced after 4-week training of wrist. And the cortical activity change was associated with inducing reorganization of motor cortex networks Conclusion: We developed bilateral wrist robotic device and robot-assisted wrist training system. Robot-assisted wrist training system showed improvement of upper limb function after training of wrist. Our system might be efficient robot-assisted wrist training for improving muscle strength, motor performance, and cortical reorganization in patients with chronic hemiplegic stroke and contribute to the development of translational research in rehabilitation robot.